Primary care medicine office evaluation and management of the adult patient - Goroll, Allan H.; Mulley, Albert G. (Wolters Kluwer, 2021)
This book addresses the full spectrum of clinical problems encountered in the adult primary care practice. It provides a review of best evidence integrated with considerations of affordability, cost-effectiveness, convenience and patient preference.